Data relating to Evaluation of the implications and efficacy of proposed changes to haloacetic acid drinking water regulation - Grundy, Polly; Goslan, Emma H.; Jarvis, Peter; Jefferson, Bruce (Cranfield University, 2026)
As an increasing number of countries move towards regulatory control of haloacetic acids (HAAs) in drinking water, there is a need to better understand the current levels, and areas where compliance will be more challenging. This study collated the available UK data and assessed the implications of adopting a standard for five HAAs (HAA5, as implemented in regions including the EU, the US and Scotland) or expanding regulation to include all nine chlorinated and brominated HAAs (HAA9, not yet implemented but proposed for England and Wales and considered in the US). In treated water samples, high levels of compliance were reported, with 99.7% of samples below the proposed standard of 80 μg/L for HAA9 and 99.2% within that of 60 μg/L for HAA5. The suitability of HAA5 as a surrogate for HAA9 was assessed and a good linear correlation between them observed in treated water (R2 = 0.94). However, correlation between HAA5 and the unregulated brominated HAAs was poor (R2 = 0.03), and consequently only information about the currently unregulated HAAs can identify where HAA9 compliance will diverge from that of regulated DBPs. Notably, while within this study compliance with proposed legislation was determined primarily by the formation of chlorinated HAAs, when a risk-based approach was taken brominated HAAs were the dominant influence. Consequently, this work highlighted that the ratio between bromide and carbon is key for the controlling the DBP risk from chlorinated water, and an improved understanding of the levels of brominated HAAs is crucial for identifying this risk.
Keywords: Haloacetic acids; drinking water; disinfection by-products; UK; HAA9